2021
DOI: 10.1021/acsomega.1c02646
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Cu-O-Si Phase in the Cu-SiO2/Si(111) System: Growth, Elemental, and Electrical Studies

Abstract: We investigate here the strain-induced growth of Cu at 600 °C and its interactions with a thermally grown, 270 nm-thick SiO2 layer on the Si(111) substrate. Our results show clear evidence of triangular voids and formation of triangular islands on the surface via a void-filling mechanism upon Cu deposition, even on a 270 nm-thick dielectric. Different coordination states, oxidation numbers, and chemical compositions of the Cu-grown film are estimated from the core level X-ray photoelectron spectroscopy (XPS) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 86 publications
(196 reference statements)
0
2
0
Order By: Relevance
“…One possible factor that may have affected these results is the diffusion of copper atoms across the Si/SiO 2 interface, which can alter the monolayer integrity and, thus, contribute to ALD nucleation. However, the diffusion of copper across dielectrics has been shown to have onset temperatures typically higher than 100 • C, which was the temperature of our ALD reactor [56][57][58][59]. Hence, it is unlikely that the diffusion of copper significantly affected our observations.…”
Section: Resultsmentioning
confidence: 87%
“…One possible factor that may have affected these results is the diffusion of copper atoms across the Si/SiO 2 interface, which can alter the monolayer integrity and, thus, contribute to ALD nucleation. However, the diffusion of copper across dielectrics has been shown to have onset temperatures typically higher than 100 • C, which was the temperature of our ALD reactor [56][57][58][59]. Hence, it is unlikely that the diffusion of copper significantly affected our observations.…”
Section: Resultsmentioning
confidence: 87%
“…From Figure S9a, it can be observed that the fitted O 1s spectra show Si–O and Cu–O–Zn/Zr bonds on the calcined CZZ-MSS, Si–O and O–Zn/Zr bonds on the calcined ZZ-MSS, and finally Si–O and O–Cu bonds on the calcined C-MSS. After the CO 2 hydrogenation reaction, all of the above-mentioned bonds were shifted to lower binding energies, and the intensities of the Cu–O–Zn/Zr bond in CZZ-MSS, O–Zn/Zr bond in ZZ-MSS, and O–Cu bonds in the calcined C-MSS were decreased and even disappeared (Figure S9b), further implying the presence of robust Cu-ZnO/ZrO 2 interface on the CZZ-MSS catalyst. High-resolution Si 2p peaks and their fitted peaks are shown in Figure S9c,d. The main peaks at the range of 103.2–104.2 eV correspond to the Si 4+ state in the bulk SiO 2 support. , It was observed that the fitted Si 2p curves of the fresh CZZ-MSS appeared with a small peak at 101.3 eV, which stands for the Si x + species at the interfaces of Si–O–Zn/Zr.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Ordered 2-dimensional (2D) Cu nanostructures on Si(111) have been reported for very low thicknesses by Zang et al [16]. In the recent years, a huge volume of work has been reported on diffusion studies of Cu in Si substrates [1741]. In most of the studies on the growth of Cu nanostructures on the silicon substrate, the films are deposited at room temperature and post annealed for preparation of nanostructures.…”
Section: Introductionmentioning
confidence: 99%